2020
DOI: 10.1155/2020/8847144
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three-Dimensional Speckle Tracking Echocardiography Parameters in Predicting Left Ventricular Remodeling

Abstract: Three-dimensional speckle tracking echocardiography (3D STE) is an emerging noninvasive method for predicting left ventricular remodeling (LVR) after acute myocardial infarction (AMI). Previous studies analyzed the predictive value of 3D STE with traditional models. However, no models that contain comprehensive risk factors were assessed, and there are limited data on the comparison of different 3D STE parameters. In this study, we sought to build a machine learning model for predicting LVR in AMI patients aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
3
0
1
Order By: Relevance
“…A recent investigation involving 255 STE-ACS patients undergoing PCI demonstrated that 3D-LVGLS was the strongest predictor of LV reverse remodeling (OR = 1.43, p = 0.02) and major adverse cardiac events (OR = 1.44, p < 0.0001), being superior to bidimensional LVGLS for the prediction of outcome [ 89 ]. Similar results on 3D strain as the index of future LV reverse remodeling were showed in another STE-ACS cohort [ 90 ].…”
Section: 3d Strainsupporting
confidence: 79%
“…A recent investigation involving 255 STE-ACS patients undergoing PCI demonstrated that 3D-LVGLS was the strongest predictor of LV reverse remodeling (OR = 1.43, p = 0.02) and major adverse cardiac events (OR = 1.44, p < 0.0001), being superior to bidimensional LVGLS for the prediction of outcome [ 89 ]. Similar results on 3D strain as the index of future LV reverse remodeling were showed in another STE-ACS cohort [ 90 ].…”
Section: 3d Strainsupporting
confidence: 79%
“…IHD occurring due to blocked coronary arteries has become one of the leading causes of morbidity and mortality in the world [ 5 , 18 ]. Reperfusion therapy is a double-edged sword that can restore the coronary blood flow to prevent the ischemic cardiomyocytes from injury but can also result in extra damage to the cardiomyocytes, which is called MI/RI [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the detailed mechanism of MI/RI is unclear. Anti-MI/RI strategies and the development of more effective cardioprotective strategies are the focuses of drug development [ 5 ]. Consequently, it is increasingly imperative to search for drugs for the treatment of MI/RI.…”
Section: Introductionmentioning
confidence: 99%
“…Застосування випадкового лісу для класифікації даних СТЕ є не новим. У роботі [15] цей алгоритм був порівняний з іншими методами машинного навчання, такими як: дерево прийняття рішень, XGBoost, наївний байєсівський класифікатор, метод k-найближчих сусідів 67 67 Рисунок 8: Дерево випадкового лісу класифікації для позиції "long" з нульовою дозою добутаміну Рисунок 9: Дерево випадкового лісу класифікації для позиції "long" без ураховування доз добутаміну та логістична регресія. Модель випадкового лісу дала найкращий результат (90,5 % точності) на тестовій вибірці у задачі розпізнавання патології серця за даними СТЕ.…”
Section: обговоренняunclassified